Los recursos didácticos y su incidencia en el proceso de enseñanza y aprendizaje en el área de lengua y literatura de los estudiantes del sexto año de educación general básica de la escuela “18 de octubre” cantón Quevedo, periodo lectivo 2021-2022 - Crespo Barragán, Mirian Lizzet (2022)
The use of didactic resources in current education is important since it allows the student to acquire significant learning in which he/she can achieve good relations with the teacher. In this sense, the objective of this research is to define the incidence of the use of didactic resources in the scholastic performance of the students of the School of Basic Education. The methodology is based on an exploratory-descriptive research, with a bibliographic and field research modality. A and B students of the evening school day belonging to the Elementary School. This study will allow teachers to strengthen their knowledge on the use of didactic resources and how they complement each other in the teaching-learning process, facilitating the development of activities, awakening the interest of students, allowing them to achieve significant knowledge that enables the development of various skills in students.